Effect of Smoking on Advanced Stage Cervical Cancer Patient Survival - Bram Pradipta; Andrijono Andrijono; Ahmad Fuady (Indonesian Journal of Obstetrics and Gynecology, 2015)
Objective: The researchers aim to investigate the relationship between smoking habit and other factors as prognostic factors of cervical cancer. Method: We performed a retrospective and prospective cohort study with subjects that are stage IIB-IVB cervical cancer patients in Dr. Cipto Mangunkusumo Hospital followed up from August 2009 to April 2014. The subjects’medical records were reviewed, and patients were interviewed about their current condition by telephone. Questions asked include smoking habit, spouse’s smoking habit, and mortality status. Patients that could not be contacted by phone were excluded from the study. Statistical analysis was done using Stata 10. Result: Out of 390 cervical cancer patients stage IIB-IVB in 2009, there were 270 patients (69.2%) that were included in the inclusion criteria. Most of the patients are 40-59 years old (82.2%) and are nonsmokers (91.8%). The most frequent clinicopathological characteristic is IIIB (63.3%) and squamous cell carcinoma (71.9%). The 5- year survival rate is 22.6%. There is no statistical significance between advanced stage cervical cancer survival with the patients’ or patients’ husbands’ smoking habit. Conclusion: In our study, smoking habits do not aggravate survival rate of advanced stage cervical cancer patients but further research must be done with more sample. Stage, and tumor size both by physical examination and ultrasound can be used as the prognostic factor. [Indones J Obstet Gynecol 2015; 3: 170-176] Keywords: Brigmann Index, cervical cancer, smoking, survival